COMBINATION OF WOBBLE BOARD AND CORE STABILITY EXERCISE MORE IMPROVES BODY BALANCE - Anjasmara, Bagas (Sport and Fitness Journal, 2021)
Introduction: Lack of physical activities or sedenetary lifestyle will affect the abilities of body, one of them is body balance, which causes several problems that are related with motor skills and one of them is increased possibililty of injury as the result of the muscle is not accustomed to hold weight more than normal activities. Improving body balance can be done by training muscles which have function to maintain the balance. Research Objectives: This study aims to identify the combination of wobble board exercise and core stability exercise is better compared to calf raise exercise and core stability exercise in improving body balance of students with love physical activities. Methods: This research used experimental methods pre and post test two group design with. The experimental group was given wobble board exercise and core stability exercise, while the control group was given calf raise exercise and core stability exercise. The number of sample in each group is 18 people and each of the group was given 3 times in a week of exercise for 6 weeks. The balance measurement in this study used standing stork test. Result: The research result is the body balance Experimental Group is increase with mean pre test score is 10,80±4,64 seconds becomes 26,51±5,41 seconds during post test, and p = 0,001. In Control Group, there is an increase body balance with mean pre test 8,39±4,51 becomes 20,54±5,18 during post test  and p = 0,001. There is a significant difference in the increase of body balance in Experimental Group and Control Group with p = 0,002 (p < 0,05). Conclusion: The combination of wobble board exercise and core stability exercise is better than the combination of calf raise exercise and core stability exercise in improving body balance of students with low physical activities. Keywords: Body Balance; Low Physical Activities; Wobble Board Exercise ; Calf Raise Exercise; Core Stability Exercise